On the belgicisms in Le Mariage de Mlle Beulemans - Bidaud, Samuel (Romanica Olomucensia, 2016)
This article focuses on the belgicisms which are present in Le Mariage de Mlle Beulemans, Frantz Fonson and Fernand Wicheler's famous comedy, which was enormously successful in Belgium as well as in France at the beginning of the last century. Belgicisms are very numerous in Le Mariage de Mlle Beulemans, but have not been studied in an exhaustive way until now, although the play is often cited in the Dictionaries of belgicisms. We first study the morphosyntactic belgicisms, and then the lexical belgicisms of Le Mariage de Mlle Beulemans.
Keywords: belgicisms; Le Mariage de Mlle Beulemans; Frantz Fonson; Fernand Wicheler; variation of the French language.